Sorotan Fundamentalisme Islam Terhadap Kepala Sekolah Perempuan - Susilawati, Susilawati; Danil, Ilham (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Abstract The creation of Siti Hawa from the ribs of the prophet Adam is a sign that women are physically weaker than men. Therefore also the background so that they often get unfair treatment or discrimination. But over time, the signal has faded, especially in Indonesia. This fact is inseparable from the services of a female emancipation warrior, RA Kartini. Today many women are as successful as men. No longer can the number of those who hold the reins of leadership be counted, one of them being the headmaster in various educational institutions, ranging from the lowest level of education to tertiary education. Whereas leadership positions in the education sector are very urgent and determine whether or not the vision, mission and goals of education are achieved or not. An in-depth study of opinions which states that